Manajemen Konflik Pada Kepemimpinan Kolektif BPK-P2L Pondok Pesantren Lirboyo Kediri - Zaenal Arifin (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2018)
This article is the result of a study that discusses conflict management implemented in the collective leadership of the Lirboyo Kediri Islamic Boarding School. Where the Lirboyo Kediri boarding school is one of the largest pesantren in the province of East Java and has also existed for more than a century and now its leadership is in the hands of the 4th generation who is the grandson of the founder of the pesantren. In carrying out its leadership, the Lirboyo Kediri boarding school uses a collective leadership style incorporated in a forum called BPK-P2L (Lirboyo Kediri Islamic Boarding School Board of Trustees). The results of this study conclude first, that the formation of the Lirboyo Kediri BPK-P2L Islamic Boarding School has the motive to maintain the integrity of the zealous ties of the pesantren. Second, the map of potential conflicts in the Lirboyo Kediri boarding school consists of: 1). The Lirboyo Kediri boarding school has unit boarding schools that are independent and have their own caregivers and organizations but on the other hand must also comply with the BPK-P2L decision, 2). Term of pondok kulon and pondok wetan. Third, that in conflict control BPK-P2L Lirboyo Kediri applies the musayawarah approach, the division of roles and authority, and applies the tradition of marriage between relatives.